Peran Brand Trust, Facilitating Condition, Dan Behavioral Intention Terhadap Minat Investasi Pada Mobile Banking - Caesar Rosyad Achmadi; Arief Nurrahman; Agatha Saputri; R. Andro Zylio Nugraha (Jurnal Manajemen Bisnis Era Digital, 2024)
Investment is an activity of placing funds owned by a person in a certain period with the hope that it will generate profits or increase the value of the investment in the future. This study aims to determine the effect of four variables that are thought to encourage the intention to invest using mobile banking, namely brand trust, facilitating conditions, and behavioral intention. This research is descriptive quantitative research. The research sample was 151 students of the Faculty of Economics and Business, Yogyakarta State University using purposive random sampling method. The research instrument was tested for content validity according to experts, construct using Exploratory Factor Analysis (EFA) and reliability coefficient using Cronbach Alpha. Processing of research data using SEM PLS. The results of this study are brand trust does not significantly affect behavioral intention and use intention of mobile banking investment features. Facilitating conditions have a significant positive effect on behavioral intention and use intention of mobile banking investment features. And behavioral intention has a significant positive effect on the use intention of mobile banking investment features. The managerial implication of this research is that banking marketers with a mobile banking base should create a marketing communication strategy regarding easy access to investment features and investment literacy using mobile banking. So that customers or bank customers will have a high interest in using investment features with mobile banking.